Kinetics and Novel Degradation Pathway of Permethrin in Acinetobacter baumannii ZH-14 - Zhan, Hui; Wang, Huishan; Liao, Lisheng; Feng, Yanmei; Fan, Xinghui; Zhang, Lianhui; Chen, Shaohua (Frontiers in Microbiology, 2018)
Persistent use of permethrin has resulted in its ubiquitous presence as a contaminant in surface streams and soils, yet little is known about the kinetics and metabolic behaviors of this pesticide. In this study, a novel bacterial strain Acinetobacter baumannii ZH-14 utilizing permethrin via partial hydrolysis pathways was isolated from sewage sludge. Response surface methodology based on Box-Behnken design of cultural conditions was used for optimization resulting in 100% degradation of permethrin (50 mg•L-1) within 72 h. Strain ZH-14 degraded permethrin up to a concentration of 800 mg•L-1. Biodegradation kinetics analysis indicated that permethrin degradation by this strain was concentration dependent, with a maximum specific degradation rate, half-saturation constant and inhibition constant of 0.0454 h-1, 4.7912 mg•L-1 and 367.2165 mg•L-1, respectively. High-performance liquid chromatography and gas chromatography-mass spectrometry identified 3-phenoxybenzenemethanol and 3-phenoxybenzaldehyde as the major intermediate metabolites of the permethrin degradation pathway. Bioaugmentation of permethrin-contaminated soils with strain ZH-14 significantly enhanced degradation, and over 85% of permethrin was degraded within 9 days with the degradation process following the first-order kinetic model. In addition to degradation of permethrin, strain ZH-14 was capable of degrading a large range of synthetic pyrethroids such as deltamethrin, bifenthrin, fenpropathrin, cyhalothrin and beta-cypermethrin which are also widely used pesticides with environmental contamination problems, suggesting the promising potentials of A. baumannii ZH-14 in bioremediation of pyrethroid-contaminated terrestrial and aquatic environments.